The Pillar of Death is Not Insurance - Maulana, Agus; Arifin, Zainal (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This paper seeks to provide a new model in the development of the Pillars of Death that occurs in the community to be incorporated in the basic principle of mutual cooperation and the ability of community contributions to be facilitated in BPJS Health and Death with implications for health care costs and death benefits. Methodology/approach – The method used in this research is a Research Literature Study with qualitative analysis based on secondary data that occurred in the last five years in Indonesia. Findings – It was found that. The findings obtained in this scientific work are a model of solutions faced by many people in dealing with health and death within a framework of achieving the Mandate of People's Prosperity Ideals that are socially just and reduce the economic burden on society and harmony. Novelty/value – As the sustainability of the Death Law Program which has similarities and differences with Insurance, in the solution to the merger of BPJS Health and Death due to the community's ability to pay contributions in the spirit of mutual cooperation. Keywords Pillars of Death, Insurance, Contributions, BPJS.